Y= -x+4
2x+2(-x+4)=8
2x-2x+8=8
8=8
x+y= 4
2x+2y= 8
-2x-2y= -8
2x+2y= 8
0=0
the answer is b inconsistent
2(6x+20) +2(8x-16)=180
12x+16x+40-32=180
28x+8=180
X=180-8/28=6
I think so my calculation may be wrong )
Answer:
3x² + x - 3
Step-by-step explanation:
The way I like to do it is to get rid of the x's and just use the numbers in the case of synthetic division
Pretend the square root of the division symbol
-4 √ 3 12 1 -12
Quick note: We're dividing by -4 because we're dividing by x + 4
First bring down the 3
-4 √ 3 13 1 -12
3
Multiply it by 4 then bring add it to the next number
-4 √ 3 13 1 -12
-12
3 1
Add that number to the next one
-4 √ 3 13 1 -12
-12 -4
3 1 -3
Finally repeat the step for the last number
-4 √ 3 13 1 -12
3 -12 -4 +12
3 1 -3 0
Now take those bottom numbers and add back the x's but with one less power, so the starting x³ would now become x², x² would become x, and so on
3x² + 1x - 3
Answer:
Io
Step-by-step explanation:
Earth's moon makes a person weigh about 1/6 of their Earth weight. Io makes a person weigh more than that, because 1/6 of 150 pounds is 25 pounds.
Answer 6
4x -2y +3z^4
4(0) - 2(1) + 3(2)^4
0 - 2 + 24
Answer7